Study on the Chemical Constituents and Anti-Migraine Activity of Supercritical CO2 Extracts of Zanthoxylum schinifolium - Yuan, Ruifang; Shi, Yunzhen; Zhang, Jinming; Hu, Qi; Wei, Xichuan; Luo, Chuanhong; Wu, Yi; Yang, Jinhui; Yang, Ming; Wang, Fang; Zheng, Chuan; Zhang, Dingkun (Frontiers in Pharmacology, 2021)
Background: Zanthoxylum schinifolium is a common herbal medicine in Southwest China. It is also a condiment commonly used in many families. In Chinese folk, Zanthoxylum schinifolium is considered to have the effect of relieving migraine, but there is no modern evidence on its anti-migraine mechanism. Objective: The aim of this study was to investigate the chemical constituents of the carbon dioxide (CO2) supercritical extracts of Zanthoxylum schinifolium (ZSSE) and its effects on migraine animals. Materials and Methods: Supercritical CO2 extraction technology was applied to extract the dried fruit of Zanthoxylum schinifolium, and the chemical components were determined by GC-MS. Two migraine animal models were established by subcutaneous injection of nitroglycerin (NTG) and reserpine respectively to further evaluate the therapeutic effect of ZSSE and explore its mechanism. On the basis of the experimental results, the therapeutic effects of linalool in different dosages and different ways of administration on NTG - induced migraine rats have been further investigated. Results: About 125 peaks were detected in ZSSE, and relative amounts of linalool alone was 74.16%. ZSSE decreased the number of head scratching significantly, the levels of serum nitric oxide (NO), endothelin-1 (ET-1), calcitonin gene-related peptide (CGRP) and the levels of interleukin-1β (IL-1β), nuclear factor kappa B (NF-κB) p65 and inhibitor of kappa B alpha (IκBα), and increased the level of 5-hydroxytryptamine (5-HT). Linalool has the potential to reduce the frequency of scratching the head and the expressions of serum NO, ET-1 and CGRP in NTG induced migraine rats. Conclusion: ZSSE has definite therapeutic effect on migraine via affecting the expression of vasomotor factors and inflammatory pathway. Linalool has been proved to be the main effective substance against migraine. These findings provide scientific basis for the development of effective and simple migraine therapy.